(Anti) Money laundering and its macroeconomic and microeconomic perspective - Danková, Diana; Šíma, Ondřej; Kováč, Michal; Vysoká škola ekonomická v Praze. Fakulta financí a účetnictví (2017)
The primary objective of this diploma thesis is to comprehensively present the issue of money laundering not only on a macro level but also in terms of commercial bank and its microeconomic response to it. The main contribution of this diploma thesis is to identify the global indicators, which should be considered when drafting strategies in the fight against the legalization of proceeds from crimes. This diploma thesis addresses the changes caused by current globalization and highlights the dangerous effects it has on evolution of this consequent criminal activity together with evaluation of its potential in the future. Due to the tense situation in Europe caused by the series of terrorist attacks, part of the work is dedicated to the explanation of the relationship between terrorist financing and money laundering.
Vedoucí práce: Ondřej Šíma
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta financí a účetnictví, 2017
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2017
Způsob přístupu: Internet
Keywords: bankovnictví a pojišťovnictví [obor dipl. práce]; diplomové práce; master's theses